Analysis of four measures of positional bias within a multiple stimulus without replacement preference assessment. (9th November 2022) - Miranda, David Ray G.; Brodhead, Matthew T.; Sipila‐Thomas, Emma S.; Fisher, Marisa H.; Plavnick, Joshua B.; Thomas, Alexandria L.; Melanson, Isaac J.
Abstract: Positional bias is a pattern of responding to a specific location that can be influenced by response effort and/or prior learning history. Prior research on positional bias within stimulus preference assessments have focused primarily on its use in paired stimulus assessments due to the complex nature of the multiple stimulus without replacement (MSWO) preference assessment. The present study is a secondary data analysis that utilized four different methods to measure side and center bias in a MSWO preference assessment for 19 young children with autism spectrum disorder. Participants displayed varying degrees of biased responding but collectively engaged in minimal biased responding. This study includes an analysis of the four methodologies, discussion of general patterns of responding, and general recommendations for the application of these methodologies in future research.